Ginsenosides: an immunomodulator for the treatment of colorectal cancer - Qian, Jianan; Jiang, Yanyu; Hu, Hongyi (Frontiers in Pharmacology, 2024)
Ginsenosides, the primary bioactive ingredients derived from the root of Panax ginseng, are eagerly in demand for tumor patients as a complementary and alternative drug. Ginsenosides have increasingly become a “hot topic” in recent years due to their multifunctional role in treating colorectal cancer (CRC) and regulating tumor microenvironment (TME). Emerging experimental research on ginsenosides in the treatment and immune regulation of CRC has been published, while no review sums up its specific role in the CRC microenvironment. Therefore, this paper systematically introduces how ginsenosides affect the TME, specifically by enhancing immune response, inhibiting the activation of stromal cells, and altering the hallmarks of CRC cells. In addition, we discuss their impact on the physicochemical properties of the tumor microenvironment. Furthermore, we discuss the application of ginsenosides in clinical treatment as their efficacy in enhancing tumor patient immunity and prolonging survival. The future perspectives of ginsenoside as a complementary and alternative drug of CRC are also provided. This review hopes to open up a new horizon for the cancer treatment of Traditional Chinese Medicine monomers.